Pemanfaatan Sampah Kaleng Berbahan Plastik Menjadi Furniture Jenis Dingklik - Kristiana Seftianingsih, Dina; Syahnas Paradita, Dea; Rifai, Dian Muhammad (Universitas Sahid Surakarta, 2023)
Abstract Plastic cans are often produced by toast traders or people who like food that uses bread filled with jam. These plastic cans are usually thrown away or collected and sold to waste collectors. Plastic waste will, of course, take longer to decompose and harm the ecosystem and survival. One way to reduce the impact of plastic can waste is to reuse cans into furnitures with new functions for home furnishings, such as chairs. Plastic cans are short and cannot be formed into chairs of standard sizes. A collection of plastic cans of the same size can be created into a small chair called a